HUMAN TRAFFICKING BERKEDOK PENEMPATAN TKI DI LUAR NEGERI: SEBUAH TINJAUAN HUKUM - Indah Putriadi Ziliwu (Jurnal Hukum Lex Generalis, 2025)
Human Trafficking in Indonesia, particulary involving Indonesian Migrant Workers (TKI), is a serious problem that violates human rights. Many TKI fall victim to fraud and exploitation while seeking employment abroad, particularly in countries such as Hong Kong, Taiwan, and Malaysia. Although protective laws exist, their implementation is often ineffective, and cases of online fraud continue to increase. Addressing human trafficking requires collaboration between the government, non- governmental organizations, and the community to create a safe environment through education and stricter law enforcement. This research examines the implementation of Law No. 21 of 2007 enforcement and legal protection for victims. The method used is normative juridical. Indonesia has strengthened its legal system with Law No. 21 of 2007 and Law No. 18 of 2017 to prevent and protect victims. Prevention, law enforcement, and recovery must be carried out in an integrated manner, involving all parties. Keywords: TKI, Overseas, Human Trafficking, Cambodia, National Law